PowerShell deep dives - Hicks, Jeffery (Manning, 2013)
PowerShell Deep Dives is a trove of essential techniques and practical guidance. It is rich with insights from experts who won them through years of experience. The book's 28 chapters, grouped in four parts (Administration, Scripting, Development, and Platforms), were hand-picked by four section editors: Jeffery Hicks, Richard Siddaway, Oisín Grehan, and Aleksandar Nikolić. Whether you're just getting started with PowerShell or you already use it daily, you'll find yourself returning to this book over and over.
Print version record
Keywords: Windows PowerShell (Computer program language); Windows PowerShell (Langage de programmation)